Entrepreneurial firms grow up: Board undervaluation, board evolution, and firm performance in newly public firms. (10th June 2019) - Garg, Sam; John Li, Qiang; Shaw, Jason D.
Abstract: Research Summary: An initial public offering (IPO) ushers in many changes to the organization's boards of directors, including the installation of a formal and comprehensive board leadership structure. This paper shows that higher board undervaluation, that is, the average degree to which directors' qualifications based on normatively accepted criteria for board leadership are not duly reflected in their appointments to the board chair and committee chair positions, is associated with higher director turnover, and with lower qualifications among new directors in the subsequent years. Further, the effect of board undervaluation on firm performance is mediated both by director turnover and new directors' qualifications. But these two mediators operate as opposite forces on performance—director turnover is associated with lower firm performance, but counter‐intuitively lower new‐director‐qualifications are associated with higher firm performance. Managerial Summary: How should a privately‐held entrepreneurial firm design its board leadership structure at IPO? What are the implications for board evolution and even firm performance? We find that higher board undervaluation, that is, the average degree to which directors' qualifications based on normatively accepted criteria for board leadership are not duly reflected in their appointments to the board chair and committee chair positions, is associated with higher director turnover, and with lower qualifications among new directors in the subsequent years. These two evolutionary paths act in opposite ways on performance—director turnover lowers firm performance, but lower new‐director‐qualifications improve firm performance. This has important implications for boards, investors, and stock exchange guidelines on board leadership structure.